The Role of Facilitator in the Implementation of Program Keluarga Harapan (PKH) in Small Island (Case Study in Hiri Island District, Ternate City – North Maluku) - Agus Salim Fuadi; Sanggar Kanto; Sholih Muadi (Wacana Journal of Social and Humanity Studies, 2017)
Abstract This research describes the other side in the implementation of Program Keluarga Harapan (PKH). This program refers to one of many poverty mitigation programs which can afford the poor (beneficiary) in urban and rural areas by giving grant-in-aid to education and health sectors due to the capacity of these sectors in suppressing poverty rate. The location of research is Hiri Island District, North Maluku Province, East Indonesia. Research focuses on the role of facilitator in the implementation of Program Keluarga Harapan, main substance to discuss is empowerment. Method of research is qualitative using case study. Research has found that the implementation of PKH in small island is not yet optimum despite the claim of its capacity to reduce poverty rate. Responsibility and good supervision from facilitator and participant are the key of successful program implementation.